1-(2,3,4-Trihydroxybenzylidene)thiosemicarbazide - Shawish, Hana Bashir (International Union of Crystallography, 2010)
In the title molecule, C(8)H(9)N(3)O(3)S, the thiosemicarbazide =N—NH—C(=S)—NH— fragment is twist a different degree of twist in the three independent molecules [dihedral angles = 7.6 (1), 11.6 (1) and 20.7 (1)°]. Intramolecular O—H⋯N and O—H⋯O hydrogen bonds occur. In the crystal, the hydroxy and amino groups are hydrogen-bond donors and the O—H⋯O, O—H⋯S and N—H⋯O hydrogen bonds generate a layer motif.